Middle Frontal Gyrus and Area 55b: Perioperative Mapping and Language Outcomes - Hazem, Sally Rosario; Awan, Mariam; Lavrador, Jose Pedro; Patel, Sabina; Wren, Hilary Margaret; Lucena, Oeslle; Semedo, Carla; Irzan, Hassna; Melbourne, Andrew; Ourselin, Sebastien; Shapey, Jonathan; Kailaya-Vasan, Ahilan; et al. (Frontiers in Neurology, 2021)
Background: Simplistic approaches to language circuits are continuously challenged by new findings in the brain structure and connectivity. The posterior middle frontal gyrus, and area 55b in particular (pMFG/area55b), has gained a renewed interest in the overall language network. Methods: Retrospective single centre cohort study of patients who have undergone awake craniotomy for tumour resection. Navigated transcranial magnetic simulation, tractography, and intraoperative findings were correlated with language outcomes. Results: Sixty-five awake craniotomies were performed between 2012 and 2020, and twenty-four patients were included. nTMS elicited 42 positive responses, 76.2% in the Inferior Frontal Gyrus (IFG), hesitation was the most common error (71.4%). In the pMFG/area55b, there were 7 positive errors (5 hesitations and 2 phonemic errors). This area had the highest positive predictive value (43.0%), negative predictive value (98.3%), sensitivity (50.0%), and specificity (99.0%) among all the frontal gyri. Intraoperatively, there were 33 cortical positive responses – 2 (6.0%) in the Superior Frontal Gyrus (SFG), 15 (45.5%) in the MFG, and 16 (48.5%) in the IFG . 29 subcortical positive responses were elicited – 21 in the deep IFG-MFG gyri and 8 in the deep SFG-MFG gyri. The most common errors identified were speech arrest at the cortical level (20 responses – 13 in the IFG and 7 in the MFG) and anomia at the subcortical level (9 patients – 8 in the deep IFG-MFG and 1 in the deep MFG-SFG). 83.3% of patients had a transitory deterioration of language after surgery, mainly in the expressive component (p=0.03). An increased number of gyri with intraoperative positive responses were related with better pre-operative (p=0.037) and worse post-operative (p=0.029) outcomes. The involvement of SFG-MFG subcortical area was related with worse language outcomes (p=0.037). Positive nTMS mapping in the IFG was associated with a better pre-operative language outcome (p=0.017) relating to a better performance in the expressive component whilst positive mapping in the MFG was related to a worse preoperative receptive component of language (p=0.031). Conclusion: This case series suggests that the posterior middle frontal gyrus, including area 55b, is an important integration cortical hub for both dorsal and ventral streams of language.